Emergence and Genomic Characterization of a KPC-2-, NDM-1-, and IMP-4-Producing Klebsiella michiganensis Isolate - Zhang, Yanyan; Gu, Danxia; Yang, Xuemei; Wu, Yuchen; Liu, Congcong; Shen, Zhangqi; Zhang, Rong (Frontiers in Microbiology, 2022)
A rectal swab sample was collected from a patient with Guillain-Barré syndrome and enriched in lysogeny broth. Carbapenem-resistant bacteria were selected by China Blue agar plates containing 0.3μg/mL meropenem. Carbapenemase-producing K. michiganensis was identified and characterized by MALDI-TOF, immune colloidal gold technique, a conjugation experiment, PCR analysis and antimicrobial susceptibility testing. The genome of K. michiganensis was determined by whole genome sequencing. Antimicrobial susceptibility testing showed that the K. michiganensis was resistant to imipenem, meropenem, ertapenem, cefmetazole, ceftazidime, cefotaxime, piperacillin/tazobactam, sulbactam/cefoperazone, ceftazidime/avibactam, cefepime, aztreonam, whereas susceptible to polymyxin B, ciprofloxacin , tigecycline and amikacin. Immune colloidal gold technique suggested that this strain co-produced three different carbapenemases (KPC, NDM and IMP). Whole genome sequencing analysis indicated that this strain belonged to ST91, and blaKPC-2, blaNDM-1 , blaIMP-4 were carried on different conjugative plasmids. Besides, the co-existence and transferability of blaKPC-2, blaNDM-1, blaIMP-4 in K. michiganensis facilitates the potential horizontal dissemination and nosocomial spread of resistance genes among multidrug-resistant.